A high-resolution study of the different surface state effects on the corrosion behaviors of a ferritic steel and an austenitic steel in supercritical water. (December 2022) - Chen, K.; Wang, J.; Zhang, L.; Wang, H.; An, X.; Li, Y.; Zhang, J.; Shen, Z.; Zeng, X.
Abstract: The corrosion behaviors of two iron-based steels in 600 ºC deaerated supercritical water (SCW) were investigated to study the effect of surface finishing. For the austenitic stainless steel (Fe-19Cr-9Ni), grinding significantly enhanced the oxidation resistance by favoring the formation of a thin and continuous chromia layer. This is because that grinding induced ultra-fined grain layer with a high dislocation density promotes the outward Cr diffusion, thus favors the transition from internal to external oxidation. For the ferritic steel (Fe-9Cr), the oxidation rate remained at a high level regardless of the surface condition mainly because the Cr diffusivity is already high enough but the Cr content is too low to promote the internal-external oxidation transition. Highlights: For the polished surfaces, a thick duplex oxide scale is revealed for both steels. Grinding significantly enhances the oxidation resistance of Fe-19Cr-9Ni steel. The oxidation rate is identical for polished and ground Fe-9Cr steel because of its low Cr content.